Human bone marrow-derived stem cells acquire epithelial characteristics through fusion with gastrointestinal epithelial cells. - Jonathan Ferrand; Danièle Noël; Philippe Lehours; Martina Prochazkova-Carlotti; Lucie Chambonnier; Armelle Ménard; Francis Mégraud; Christine Varon (PLoS ONE, 2011)
Bone marrow-derived mesenchymal stem cells (MSC) have the ability to differentiate into a variety of cell types and are a potential source for epithelial tissue repair. Several studies have demonstrated their ability to repopulate the gastrointestinal tract (GIT) in bone marrow transplanted patients or in animal models of gastrointestinal carcinogenesis where they were the source of epithelial cancers. However, mechanism of MSC epithelial differentiation still remains unclear and controversial with trans-differentiation or fusion events being evoked. This study aimed to investigate the ability of MSC to acquire epithelial characteristics in the particular context of the gastrointestinal epithelium and to evaluate the role of cell fusion in this process. In vitro coculture experiments were performed with three gastrointestinal epithelial cell lines and MSC originating from two patients. After an 8 day coculture, MSC expressed epithelial markers. Use of a semi-permeable insert did not reproduce this effect, suggesting importance of cell contacts. Tagged cells coculture or FISH on gender-mismatched cells revealed clearly that epithelial differentiation resulted from cellular fusion events, while expression of mesenchymal markers on fused cells decreased over time. In vivo cell xenograft in immunodeficient mice confirmed fusion of MSC with gastrointestinal epithelial cells and self-renewal abilities of these fused cells. In conclusion, our results indicate that fusion could be the predominant mechanism by which human MSC may acquire epithelial characteristics when in close contact with epithelial cells from gastrointestinal origin . These results could contribute to a better understanding of the cellular and molecular mechanisms allowing MSC engraftment into the GIT epithelium.